Optimized electric power distribution via genetic algorithm based estimation / Otonye Ene Ojuka ... [et al.] - Ojuka, Otonye Ene; Wokoma, Biobele Alexander; Bala, Tekena Kashmony; Kinba, Queen Blue-Jack; Tamunobelema, Asime (UiTM Press, 2024)
Power losses will always occur during the distribution of electricity, no matter how carefully distribution lines are designed. Cutting out these losses in lines to a minimal level will improve the efficiency of the supply of electricity and also add financial and economic value to the host nation. This research shows an effective way of minimizing power loss in distribution lines using optimal capacitor placement (OCP) in conjunction with a genetic algorithm (GA). The Electrical Transient Analyzer Program (ETAP) was used for simulation with the Choba 11kV feeder as a case study. The load flow analysis carried out using the Newton-Raphson method showed that 67 out of the 76 buses were critically and marginally loaded, leading to a low voltage profile below the IEEE-prescribed limit of ±5%. To improve the performance of the entire network and minimize losses, the GA powered OCP model on ETAP strategically deployed appropriate reactive power through capacitor banks at its best location. The load flow results after enhancement showed an improved voltage profile, and the losses in the network were significantly reduced to the tune of 12% reduction, with a huge annual profit of from the second year. Cumulatively, the expected total capacitor operational cost, loss reduction savings, and profit for the planning period are $58,000, $304,323.5, and $83,523.46, respectively.